2017
DOI: 10.1016/j.polymer.2017.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Block copolymer compatibilized polymer: fullerene blend morphology and properties

Abstract: Recent studies have shown the role of block copolymer as compatibilizer in tuning the phase separated morphology of the active layer so as to improve the overall photovoltaic efficiency of organic photovoltaic (OPV) devices. Here, we substantiate this observation by investigating the role of a rod-coil block copolymer poly-(3-hexylthiophene)-b-polystyrene (P3HT-b-PS) as compatibilizer in influencing the blend morphology and device performance of several polymer:fullerene blend systems. Fullerene derivatives N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Block copolymers incorporating both P3HT and poly(styrene) portions are well-known polymeric CBs, widely reported to improve the morphology of P3HT blends in combination with PCBM [140] or other fulleropyrrolidine derivatives [141]. An "exotic" approach has been recently referred to by Mohammadi-Arbati and colleagues, who have reported the combined addition of a rod-coil block copolymer comprising P3HT and polystyrene (P3HT-b-PS), and reduced graphene oxide nanosheets grafted with regioregular poly(3-hexylthiophene) (rGO-g-P3HT) as compatibilizers in a typical P3HT:PCBM blend [142].…”
Section: Thiophene-containing Polymeric Cbsmentioning
confidence: 99%
See 1 more Smart Citation
“…Block copolymers incorporating both P3HT and poly(styrene) portions are well-known polymeric CBs, widely reported to improve the morphology of P3HT blends in combination with PCBM [140] or other fulleropyrrolidine derivatives [141]. An "exotic" approach has been recently referred to by Mohammadi-Arbati and colleagues, who have reported the combined addition of a rod-coil block copolymer comprising P3HT and polystyrene (P3HT-b-PS), and reduced graphene oxide nanosheets grafted with regioregular poly(3-hexylthiophene) (rGO-g-P3HT) as compatibilizers in a typical P3HT:PCBM blend [142].…”
Section: Thiophene-containing Polymeric Cbsmentioning
confidence: 99%
“…One very recent example concerning a P3HT:PCBM OPV device looks interesting for opening discussion over some "confusing" terminology. In the paper from Xu and coworkers [143], they describe an OPV based on the classic architecture P3HT:PCBM, where a compatible low-bandgap polymer is added, PCBTDPP, in order to act as a "bridge" between the main donor and acceptor units, Block copolymers incorporating both P3HT and poly(styrene) portions are well-known polymeric CBs, widely reported to improve the morphology of P3HT blends in combination with PCBM [140] or other fulleropyrrolidine derivatives [141]. An "exotic" approach has been recently referred to by Mohammadi-Arbati and colleagues, who have reported the combined addition of a rod-coil block copolymer comprising P3HT and polystyrene (P3HT-b-PS), and reduced graphene oxide nanosheets grafted with regioregular poly(3-hexylthiophene) (rGO-g-P3HT) as compatibilizers in a typical P3HT:PCBM blend [142].…”
Section: Thiophene-containing Polymeric Cbsmentioning
confidence: 99%
“…Accordingly, inverted devices prepared with C-PCPDTBT, which display such concentration gradient, exhibit higher performances (PCE of 3.89%) as compared to those using Si-PCPDTBT:PC 71 BM active layers (PCE of 3.17%). Note that modifying the structure is not limited to bridging atoms and synthesis of copolymers consisting of conjugated and electrically insulating blocks or functionalizing the polymer also provide means to tune the vertical concentration gradients in PSC active layers [ 60 , 61 ].…”
Section: Generation Of Vertical Ed–ea Distribution In Single Activmentioning
confidence: 99%
“…Block copolymers are promising to solve above problems because of a well-defined molecular structure [2]. Many studies have shown that the mechanical and rheological properties of various blends are remarkably improved by adopting block copolymers [3][4][5][6][7][8][9]. Similar to anionic polymerization, controlled/ living radical polymerization (CLRP) is a powerful tool to synthesize complex polymers like block copolymers and gradient copolymers, especially suitable for polar monomers [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%